Unique protein interaction networks define the chromatin remodelling module of the NuRD complex. (31st July 2021) - Sharifi Tabar, Mehdi; Giardina, Caroline; Feng, Yue; Francis, Habib; Moghaddas Sani, Hakimeh; Low, Jason K. K.; Mackay, Joel P.; Bailey, Charles G.; Rasko, John E. J.
Abstract : The combination of four proteins and their paralogues including MBD2/3, GATAD2A/B, CDK2AP1 and CHD3/4/5, which we refer to as the MGCC module, form the chromatin remodelling module of the nucleosome remodelling and deacetylase (NuRD) complex. To date, mechanisms by which the MGCC module acquires paralogue‐specific function and specificity have not been addressed. Understanding the protein–protein interaction (PPI) network of the MGCC subunits is essential for defining underlying mechanisms of gene regulation. Therefore, using pulldown followed by mass spectrometry analysis (PD‐MS), we report a proteome‐wide interaction network of the MGCC module in a paralogue‐specific manner. Our data also demonstrate that the disordered C‐terminal region of CHD3/4/5 is a gateway to incorporate remodelling activity into both ChAHP (CHD4, ADNP, HP1γ) and NuRD complexes in a mutually exclusive manner. We define a short aggregation‐prone region (APR) within the C‐terminal segment of GATAD2B that is essential for the interaction of CHD4 and CDK2AP1 with the NuRD complex. Finally, we also report an association of CDK2AP1 with the nuclear receptor co‐repressor (NCOR) complex. Overall, this study provides insight into the possible mechanisms through which the MGCC module can achieve specificity and diverse biological functions. Abstract : The protein interaction network of the remodelling module of the NuRD complex reveals paralogue‐specific interaction signatures. Paralogue‐specific interactions occur via CHD3/4/5, GATAD2A/B and MBD2/3 subunits, whilst CDK2AP1 and CHD3/4/5 are also individually found in the NCoR and ChAHP complexes, respectively.